Research and progress of focused ultrasound in the treatment of Alzheimer’s disease - Ma, Xishun; Li, Tongxia; Du, Lizhen; Han, Tongliang (Frontiers in Neurology, 2023)
Alzheimer's Disease(AD) is one of the most common degenerative diseases of the central nervous system, with progressive cognitive and memory impairment and decreased ability of daily life as the cardinal symptoms, influencing the life quality of patients severely. There are currently approximately 46 million people living with AD worldwide, and the number is expected to triple by 2050, which will pose a huge challenge for healthcare. At present, the Food and Drug Administration (FDA) of the United States has approved five main drugs for the clinical treatment of AD, which are cholinesterase inhibitors tacrine, galantamine, capalatine and donepezil, and N-methyl-d-aspartate receptor antagonist memantine, although these drugs have shown good efficacy in clinical trials, the actual clinical effect is less effective due to the existence of blood brain barrier (BBB). With the continuous development of ultrasound technology in recent years, focused ultrasound (FUS), as a non-invasive treatment technique, may target ultrasound energy to the deep brain for treatment without damaging the surrounding tissue. For the past few years, some studies could use FUS combined with microvesicles to induce BBB opening and targeted drug delivery to treat AD, providing new opportunities for the treatment of AD. This article reviews the application research and progress of focused ultrasound in the treatment of AD, in order to provide new directions and ideas for the treatment of AD.